The Experience of Plwha Who Get Social Support Undergoing in Daily Life in Malang - Setyoadi Setyoadi (Jurnal Ners, 2013)
Introduction: HIV/AIDS is a chronic disease that are different from other diseases, because of the problems caused so complex that they need social support. Support groups (self help groups) can help identify and use resources more adaptive coping. The purpose of this study to gain a deep understanding of people living with HIV experience of social support.Method: This study used qualitative methods of descriptive phenomenology with depth interviews with eight participants were diagnosed with HIV/AIDS who live in Malang Raya. Data were analyzed with a thematic analysis of transcripts of the interviews and obtained 11 themes.Result: The results showed that the three themes of HIV infection risk factors, namely: socioeconomic risk, behaviour risk, adjustment of growth and development, a theme related to the response associated with a diagnosis of HIV/AIDS namely psychosocial responses, the two themes of spiritual meaning in life is change and designing the future, a theme of support came from the social support, two themes concerning the effect of social support received is controlled health and health care, and the three themes of the support he expected, namely: health care, a form of support, and empowerment.Discusion: It is important to develop a community nurse role of social support groups in the context of nursing care and economic empowerment of people living with HIV. The recommendation based on this study is health nurses need to make a home visit program and facilitate the provision of working capital loans (micro fi nance) in PLWHA.